Inter-subspecies diversity of maize to drought stress with physio-biochemical, enzymatic and molecular responses - Eskikoy,Gokhan; Kutlu,Imren (PeerJ, 2024)
Background Drought is the most significant factor limiting maize production, given that maize is a crop with a high water demand. Therefore, studies investigating the mechanisms underlying the drought tolerance of maize are of great importance. There are no studies comparing drought tolerance among economically important subspecies of maize. This study aimed to reveal the differences between the physio-biochemical, enzymatic, and molecular mechanisms of drought tolerance in dent (Zea mays indentata), popcorn (Zea mays everta), and sugar (Zea mays saccharata) maize under control (no-stress), moderate, and severe drought stress. Methods Three distinct irrigation regimes were employed to assess the impact of varying levels of drought stress on maize plants at the V14 growth stage. These included normal irrigation (80% field capacity), moderate drought (50% field capacity), and severe drought (30% field capacity). All plants were grown under controlled conditions. The following parameters were analyzed: leaf relative water content (RWC), loss of turgidity (LOT), proline (PRO) and soluble protein (SPR) contents, membrane durability index (MDI), malondialdehyde (MDA), and hydrogen peroxide (H2O2) content, the antioxidant enzyme activities of superoxide dismutase (SOD), ascorbate peroxidase (APX), and catalase (CAT). Additionally, the expression of heat shock proteins (HSPs) was examined at the transcriptional and translational levels. Results The effects of severe drought were more pronounced in sugar maize, which had a relatively high loss of RWC and turgor, membrane damage, enzyme activities, and HSP90 gene expression. Dent maize, which is capable of maintaining its RWC and turgor in both moderate and severe droughts, and employs its defense mechanism effectively by maintaining antioxidant enzyme activities at a certain level despite less MDA and H2O2 accumulation, exhibited relatively high drought tolerance. Despite the high levels of MDA and H2O2 in popcorn maize, the up-regulation of antioxidant enzyme activities and HSP70 gene and protein expression indicated that the drought coping mechanism is activated. In particular, the positive correlation of HSP70 with PRO and HSP90 with enzyme activities is a significant result for studies examining the relationships between HSPs and other stress response systems. The discrepancies between the transcriptional and translational findings provide an opportunity for more comprehensive investigations into the role of HSPs in stress conditions.
Keywords: Antioxidant enzymes; Drought; Heat shock proteins; Maize; Membrane damage; Osmoregulation